2016
DOI: 10.1097/mnm.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of WHO, RECIST 1.1, EORTC, and PERCIST criteria in the evaluation of treatment response in malignant solid tumors

Abstract: Significant agreement was detected when the WHO, RECIST 1.1, EORTC, and PERCIST criteria were compared both within as well as between each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Intercriteria agreements between RECIST 1.1, PERCIST, and EORTC were good to excellent at SCAN-3, performed 4 mo after ICI was initiated, which is in accordance with a previous report using cytotoxic chemotherapy (19). However, interestingly, intercriteria agreement between the PET and CT modalities was not good in the early course of ICI therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Intercriteria agreements between RECIST 1.1, PERCIST, and EORTC were good to excellent at SCAN-3, performed 4 mo after ICI was initiated, which is in accordance with a previous report using cytotoxic chemotherapy (19). However, interestingly, intercriteria agreement between the PET and CT modalities was not good in the early course of ICI therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Disease response to therapy has been evaluated in multiple studies encompassing a variety of tumor types using these metrics (17)(18)(19).…”
mentioning
confidence: 99%
“…Several recent studies have compared response assessment by EORTC PET criteria and PERCIST [1722, 2427]. A meta-analysis of 6 studies including 348 patients concluded that EORTC criteria and PERCIST “showed almost perfect concordance” with a kappa of 0.946 [28].…”
Section: Clinical Experience With Eortc Criteria and Percistmentioning
confidence: 99%
“…So far, however, there only relatively few and mostly small studies comparing RECIST and PERCIST (References: [17] [42] [43] [44] [45] [46] [47] [48] [20] [49] [50] [51] [21] [52] [53] [24] [23] [25] [54] [26] [55] [56]). A meta-analysis published in 2016 identified 6 studies including 268 patients [57].…”
Section: Limitations Of Recist and Opportunities For Fdg Pet Based Rementioning
confidence: 99%
“…This treatment was continued until response evaluation criteria in solid tumors (RECIST)-defined progressive disease and cumulative toxic effects were developed, or if the patients chose to discontinue the treatment. [12] A research nurse or doctor in every center checked the toxicities of the registered medication in this study. Regarding the follow-up schedule, all patients were administered treatment on days 1, 8, and 15 every 4 weeks in subsequent cycles.…”
Section: Methodsmentioning
confidence: 99%